2023
DOI: 10.3390/nu15051156
|View full text |Cite
|
Sign up to set email alerts
|

Update of a Genetic Risk Score Predictive of the Plasma Triglyceride Response to an Omega-3 Fatty Acid Supplementation in the FAS Study

Abstract: A genetic risk score (GRS) predictive of the plasma triglyceride (TG) response to an omega-3 fatty acid (n-3 FA) supplementation has been previously developed in the Fatty Acid Sensor (FAS) Study. Recently, novel single nucleotide polymorphisms (SNPs) interacting with a fish oil supplementation and associated with plasma lipid levels have been identified in the UK Biobank. The aim of this study was to verify whether the addition of SNPs identified in the UK Biobank to the GRS built in the FAS Study improves it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Second, by adopting a categorical approach, we acknowledge the potential oversimplification of complex physiological responses, potentially masking variations in treatment effects within these broad categories. However, we have previously shown that the classification of participants into responders and non-responders constituted a major strength of the FAS Study, allowing a growing reliability in the identification of actual responders by refining the predictive models ( 8 10 , 57 , 58 ). In terms of clinical relevance, we recently reported that a prognostic model with such a high predictive performance may be a suitable decision aid tool to identify individuals likely to benefit from n-3 FA supplementation in reducing plasma TG levels ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, by adopting a categorical approach, we acknowledge the potential oversimplification of complex physiological responses, potentially masking variations in treatment effects within these broad categories. However, we have previously shown that the classification of participants into responders and non-responders constituted a major strength of the FAS Study, allowing a growing reliability in the identification of actual responders by refining the predictive models ( 8 10 , 57 , 58 ). In terms of clinical relevance, we recently reported that a prognostic model with such a high predictive performance may be a suitable decision aid tool to identify individuals likely to benefit from n-3 FA supplementation in reducing plasma TG levels ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously shown that the classification of participants into responders and non-responders constituted a major strength of the FAS Study, allowing a growing reliability in the identification of actual responders by refining the predictive models ( 8 10 , 57 , 58 ). In terms of clinical relevance, we recently reported that a prognostic model with such a high predictive performance may be a suitable decision aid tool to identify individuals likely to benefit from n-3 FA supplementation in reducing plasma TG levels ( 57 ). Nevertheless, such a predictive tool would need to be validated first in a larger and heterogeneous cohort to be able to guide treatment choices, and should emphasize sensitivity (identifying actual responders) over specificity (accurately classifying non-responders) to maximize the number of patients benefiting from n-3 FA treatment.…”
Section: Discussionmentioning
confidence: 99%